Edukasi Literasi Keuangan Pada Pelaku UMKM Desa Mojotengah, Kecamatan Bareng, Kabupaten Jombang - Faiz Firdaus Makarim; Ugy Soebiyantoro (Institut Teknologi dan Bisnis Semarang, 2023)
Financial report education is an effort to improve individual financial understanding and management through a better understanding of financial reports. Financial reports are documents that reflect the financial performance of an entity and provide important information for making decisions related to finance. This study aims to analyze the importance of financial reporting education in increasing individual understanding of financial aspects, and how this understanding can be used for better financial management. In this study, the method used was primary and secondary data collection involving surveys, interviews, and literature studies. In addition, financial report education can also help individuals develop better financial management skills. Individuals can learn about budget planning, long-term financial planning, and effective savings techniques. Based on the findings of this study, greater efforts are needed to improve financial reporting education in the community.